Kualitas Pelayanan Administrasi Pada Kelurahan Kamahedoga Kabupaten Merauke - Santi, Lila; Herman Christian Maria Sebastian Rumlus (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2025)
Public administration services at the village level play an important role in meeting the needs of the community, including the issuance of identity documents. This study was conducted in Kamahedoga Village, Merauke Regency, to determine the quality of administrative services and the factors that support and hinder them. This study used a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. The results showed that the quality of service at the Kamahedoga village office was fairly good, supported by adequate facilities and responsive staff. However, there are still obstacles in the form of low employee discipline, delays in completing documents, and a lack of transparency. Supporting factors include daily duty rosters and periodic evaluations, quick responses to community complaints, community trust in the legality of documents, orderly and systematic archive management, and good ethics and attitudes in service. Meanwhile, the inhibiting factors are low employee discipline, insufficient number of employees, lack of daily supervisors, lack of some supporting facilities, and issues of unfairness in the distribution of social assistance funds.